Infestation and distribution of the mite varroa jacobsoni in africanized honey bee (apis mellifera) colonies - Geraldo Moretto (Interciencia, 2001)
Whereas in several parts of the world varroa is the majorpest affecting apiculture, in others the parasite is unknown tomany beekeepers because of the little damage it causes to bees.The impact of the mite Varroa jacobsoni is related to the climaticconditions and the races of Apis mellifera bees in each regionwhere the pest exists. In the present study, the mite infestationlevels were assessed to determine the evolution of the pest in Africanized bee colonies in Southern Brazil. The current level ofinfestation was considered low, approximately two mites per onehundred adult bees. This result is similar to that obtained for thesame apiary almost five years ago and for others distributed invarious regions of Brazil. In the present study, on average, 61%of the total varroa population was found in the worker brood.